The Degree of Female Kindergarten Principals' Practice of Management by Values in Damascus City (Damascus University Journal of educational and Psychologyical sciences, 2021)
The study aims at identifying the degree of Kindergarten Female Principals' Practice of management by values in Damascus City and identifying the differences between the mean scores of the individuals of the sample according to the variables of dependence, educational and scientific qualification, and years of experience. To achieve the aim of the study, the researcher used the analytical descriptive approach. The inventory was applied on a sample which consisted of (306) female kindergarten principals in Damascus City in the first semester of the academic year 2018-2019. The questionnaire was applied and the results indicated the following: The degree of principals' practice of management by values was high in the questionnaire as a whole. The results also indicated that there were differences of statistical significance at the level (0.05) between the mean scores of the Kindergarten female Principals according to the dependence variable on the questionnaire as a who le in Favour of private Kindergartens. There were differences of statistical significance between the mean scores of female principals according to the scientific qualification on the questionnaire as a whole the in favour of the B.A holders. There were statistically significant differences  according the educational qualification on the whole and secondary domains in favour of the educational qualification. There  were statistically significant differences according to the variable of years of experience in favour of those who had experience more than (10years).
Keywords: The Degree of Female Kindergarten Principals' Practice of Management by Values in Damascus City